The impact of multicultural approaches on entrepreneurial education in universities: systematic review with emphasis on the strategic design of programs aimed at teacher - Libermann, Naira; Jardim, Jacinto; Nunes, Ana Cecilia Bisso (Frontiers in Education, 2026)
This article presents the results of a systematic literature review (SLR) that investigated the impact of multicultural approaches on entrepreneurship education in universities, with a special focus on how ethno-cultural principles influence the strategic design of programs aimed at teacher training. Using the PRISMA protocol, rigorous selection criteria were applied, resulting in the inclusion of 42 relevant studies. The results indicate that although multiculturalism appears sporadically in pedagogical practices of entrepreneurship education, its integration into the design of programs focused on teacher training remains incipient. The analysis highlights gaps in literature and points to the need for more integrated, critical, and intercultural approaches in the development of entrepreneurial education programs.